Exposing postdocs to multiple institutional types: a PROMISE-ing intervention to prepare biomedical faculty - Cresiski, Robin H.; Ugarte, Fadel; Harris, LaKeisha; Clark, Jessica K. (Frontiers in Education, 2024)
Biomedical faculty positions require experience as a postdoctoral scholar (or "postdoc"). However, there is a current misalignment with postdoctoral training and workforce needs within higher education. The majority of postdocs are trained to be research faculty while completing fellowships at research-intensive universities, despite the fact that the majority of US higher educational institutions (where these postdocs may be employed) focus on undergraduate education. This leads to postdoctoral scholars not having the opportunity to gain exposure to different institutional types where they could be employed. Importantly, they also lack the opportunity to build a network or receive mentorship from faculty at non-R1 institutions. This may be particularly true of underrepresented scholars. In this brief report, we describe the practice of the NSF-funded PROMISE Academy Alliance to bridge this training gap and support greater preparation for faculty careers at an array of institutional types by leveraging collaboration within a state university system. A survey of PROMISE Academy Fellows about their structured experiences engaging with other campuses (e.g., campus tours, workshops, speaking opportunities) reveals that visits to other campuses within the state system are informative and impactful, both on their research and their employment interests. The positive findings can hopefully inspire easy-to-implement changes in postdoctoral support across other university systems or regional consortia.